On the path to sustainable development: The nexus among owner gender diversity, energy management, and firms' innovation radicalness - Prokop, Viktor; Hojnik, Jana; Zapletal, David; Zizmond, Egon (Wiley-Blackwell, 2023)
This research focuses on the part of sustainable development related to energy management and thus aims to find the missing piece in research on the role of owner gender diversity (OGD) in processes of energy management (EM) introduction and the creation of radical and incremental innovation. Employing the World Bank's Enterprise Survey 2019 data covering 4646 firms from 11 European countries, we confirm the hypothesis that OGD increases firms' chance to reach radical and incremental innovation. Contrary to the majority of prior studies, we reject the hypothesis that OGD increases firms' chance to introduce EM; rather, we empirically prove the positive effects of firms' value drivers and market pressure on EM. We also confirm the link between firms' introduction of EM and the creation of radical and incremental innovations. This study expands research into the gender diversity of the upper echelons, addressing recent calls to expand open innovation research into new research categories and identify the determinants of firms' introduction of EM.
Na cestě k udržitelnému rozvoji: Spojení mezi genderovou diverzitou vlastníků, energetickým managmentem a radikálností inovací
Keywords: energy management; European countries; incremental innovation; owner gender diversity; radical innovation; sustainable development; World Bank's Enterprise Survey; energetický management; evropské země; přírůstkové inovace; genderová diverzita vlastníků; radikální inovace; udržitelný rozvoj; Světová banka